Lipid Nanoparticles-Based Therapy in Liver Metastasis Management: From Tumor Cell-Directed Strategy to Liver Microenvironment-Directed Strategy - Wang Y; Yin Z; Gao L; Ma B; Shi J; Chen H (International Journal of Nanomedicine, 2023)
Yuhan Wang,1 Zhenyu Yin,1 Lei Gao,1 Bin Ma,1 Jianming Shi,1 Hao Chen2 1Lanzhou University Second Hospital, Lanzhou, 730030, People’s Republic of China; 2Department of Surgical Oncology, Key Laboratory of the Digestive System Tumors of Gansu Province, Lanzhou University Second Hospital, Lanzhou, 730030, Gansu Province, People’s Republic of ChinaCorrespondence: Hao Chen, Tel +8615009467790, Fax +8609315109551, Email ery_chenh@lzu.edu.cnAbstract: Metastasis to the liver, as one of the most frequent metastatic patterns, was associated with poor prognosis. Major drawbacks of conventional therapies in liver metastasis were the lack of metastatic-targeting ability, predominant systemic toxicities and incapability of tumor microenvironment modulations. Lipid nanoparticles-based strategies like galactosylated, lyso-thermosensitive or active-targeting chemotherapeutics liposomes have been explored in liver metastasis management. This review aimed to summarize the state-of-art lipid nanoparticles-based therapies in liver metastasis management. Clinical and translational studies on the lipid nanoparticles in treating liver metastasis were searched up to April, 2023 from online databases. This review focused not only on the updates in drug-encapsulated lipid nanoparticles directly targeting metastatic cancer cells in treating liver metastasis, but more importantly on research frontiers in drug-loading lipid nanoparticles targeting nonparenchymal liver tumor microenvironment components in treating liver metastasis, which showed promise for future clinical oncological practice.Keywords: liver neoplasms, neoplasm metastasis, liposomes, tumor microenvironment